Marine Spatial Planning and other Area-Based Management Tools. The International Framework and Implementation in Iceland - Agnar Bragi Bragason 1977- (2024)
This research is in the fields of the law of the sea, planning law, environmental law, and natural resource law. It examines the international, European Union (EU) and Icelandic criteria of general planning in the coastal and marine environment. Planning needs and interests by States have gradually expanded from land to the coastal and marine areas. In line with the development of the law of the sea, the legal status of the oceans has generally evolved from freedom of the seas to greater exclusive national jurisdiction, being the basis for area-based management tools (ABMTs), such as marine spatial planning (MSP), integrated coastal zone management (ICZM), marine protected areas (MPAs) and other effective (area-based) conservation measures (OECMs). The need for spatial plans in the marine areas comes both from managing various and overlapping human activities in coastal and marine areas and from fulfilling international environmental commitments and obligations by States. These commitments have been developing over several decades, to protect ecosystems and biological diversity. The EU has adopted as a part of its Integrated Maritime Policy (IMP) the Marine Strategy Framework Directive (MSFD) and the Directive 2014/89/EU establishing á framework for maritime spatial planning (DMSP). The EU member States (MS) are to transpose and implement the general framework within the scope of the shared competence legal source of the EU. However, the MS have exclusive competences in the planning of land and in coastal areas, provided it is communicated in plans. Within each EU MS the pace and development of the implementation has not been completely aligned but requires the application of an ecosystem-based approach to the management of human activities enabling a sustainable use of marine goods and services. The EU is a driving force in the world regarding ocean governance with cooperation with the United Nations Educational, Scientific and Cultural Organisations (UNESCO). Independent from the EU rules, Iceland has ...